Sprengel shoulder: a case report - Das, Bipul Kumar; Deka, Debajani; Sharma, Suyashi (International Journal Of Community Medicine And Public Health, 2022)
Sprengel shoulder is a rare deformity of shoulder girdle of unknown etiology. Eulenburg in 1863, had first reported this rare congenital anomaly of the scapula. Sprengel described it in 1891, and hence this deformity got its’ name. Autosomal dominant inheritance has been reported for this abnormality. Abnormal descent of the scapula during 9th to 12th weeks of gestation leads to this congenital anomaly. It is a cosmetic deformity. Elevation of scapula is the characteristic feature. A lump at the back of the neck with restricted movements of the shoulder and or arm are the presenting finding. The affected scapula is rotated on its sagittal axis. The superior and the vertebral border comes nearer to the medial line and to the axilla respectively. Severity of this deformity varies widely being almost invisible when covered with clothes to the shoulder being elevated over 5 centimeters along with the presence of webbing of neck. This congenital deformity can be associated with other musculoskeletal abnormalities such as Klippel-Feil syndrome, scoliosis and rib anomalies. In 30% of cases of Sprengel shoulder, an omovertebral cartilaginous, fibrous or bony bar connecting superomedial border of scapula to spine, transverse process or lamina of cervical vertebra can be seen and this causes restriction of movements around the shoulder girdle. Surgical management is considered in severe cases. Surgical management involves excision of the protruding portion of scapula and inferior translation of scapula. This enhances shoulder functions as well as general appearance of the patient.